Uropygial gland volume and malaria infection are related to survival in migratory house martins. (25th September 2017) - Magallanes, S.; García‐Longoria, L.; López‐Calderón, C.; Reviriego, M.; de Lope, F.; Møller, A. P.; Marzal, A.
Abstract : Pathogens such as bacteria, fungi and malaria and related haemosporidians provoke negative effects on the fitness of their hosts. Animals have developed a range of defensive mechanisms to resist or eliminate these parasitic infections and their negative fitness costs. The uropygial gland secretion has been proposed to act as defensive barrier of skin and plumage in the fight against bacteria and fungi, and may prevent birds from acquiring haemosporidian infections. Thus, the secretion of uropygial glands of birds may favour survival of individuals. However, whether uropygial gland secretion influence survival remains unknown. Here we explore if the size of the uropygial gland and malaria infection influence survival of house martins Delichon urbica . We showed, for the first time, that the volume of the uropygial gland positively predicted survival prospects of malaria infected house martins. Malaria infected birds had the lowest probability of survival, with the effect of gland size on survival prospects depending on infection: infected house martins with larger uropygial glands were better able to survive to the next breeding season, while infected birds with small uropygial glands were not. These results highlight the importance of uropygial gland secretion in the life history of wild birds.